A study on export-oriented activities and clients handling procedures of KUEHNE+NAGEL Bangladesh Limited - Hossain, Zawad (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.